A sea of contested evidence: Disputes over coastal pollution in Hout Bay, Cape Town, South Africa - Beukes, Amy (School of African and GenderStuds, Anth and Ling, 2022)
The City of Cape Town's (CoCT) wastewater management system discharges effluent from households, industries and other sources into the Atlantic Ocean through deep-water marine outfalls in Green Point, Camps Bay and Hout Bay. At total capacity, these three outfalls discharge 55.3 megalitres (Ml) into marine receiving environments daily. With minimal pre-treatment that amounts to screening and sieving, this results in microbial and chemical pollution of the sea (including chemicals of emerging concern), marine organisms, recreational beaches, and Marine Protected Areas (MPAs). This research focuses on contestations over evidence of that pollution in Hout Bay. The study documents the work of independent scientists seeking to provide evidence of coastal pollution obtained via microbial and chemical analyses of water (coastal and inland) and marine organisms (Mytilus galloprovincialis) samples. It also presents accounts of pollution obtained via ethnographic research with local residents, fishers, frequent water users and river activists who have observed and experienced poor coastal water quality. However, the form of evidence that is considered and informs decision-making processes by the CoCT has consistently sought to invalidate these forms of evidence, from both independent scientists and the public. Debates around knowledge of water and contests over evidence that highlight the entanglements of science, politics, and ways of knowing make visible a consistent pattern in coastal water-quality governance by the City, which results in inaction regarding the ever-growing issue of coastal pollution in Cape Town.